Pengaruh Tax Planning, Aset Pajak Tangguhan dan Beban Pajak terhadap Manajemen Laba (Studi Empiris pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2018 – 2022) - Sari, Elka; Karlina, Lilis (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to analyze the influence of tax planning, deferred tax assets and tax burden on earnings management. This research was carried out by analyzing Food and Beverage companies listed on the Indonesia Stock Exchange (BEI) for the period 2018 - 2022. The sample used in this research was 84 companies using a purposive sampling method and obtained 22 sample companies with a period of 5 year so that the data analyzed amounts to 110 data. The results of the research based on the r2 test results show that the R-squared value is 0.087238 from the relationship between the independent variable and the dependent variable which has a value of 87.23% of the earnings management variable (Y) which can be explained by the influence of the independent variable tax planning (X1), deferred tax assets (X2). , and tax burden (X3), the remaining 12.77% is determined by other variables that cannot be explained or are not used in this research. And the F test results of tax planning (X1), deferred tax assets (X2), and tax burden (X3) have a simultaneous effect on earnings management (Y). Meanwhile, the T test results from tax planning (X1) have a significant effect on earnings management (Y), deferred tax assets (X2) have no significant effect on earnings.